FC079: The Race-Free EGFR Equation, The Kidney Failure Risk Equation and Referrals to Specialist Renal Clinics. (3rd May 2022) - Sullivan, Michael; Mark, Patrick; Mair, Frances; Jani, Bhautesh; Nitsch, Dorothea; Lees, Jennifer
Abstract: BACKGROUND AND AIMS: The new race-free estimated glomerular filtration rate (eGFR) was developed in 2021. Recently in the UK in keeping with similar initiatives elsewhere, the kidney failure risk equation (KFRE) to predict the risk of kidney failure has been incorporated into clinical guidelines. Referral from primary care to a specialist renal clinic is recommended if eGFR falls to < 30 mL/min/1.73 m 2 and/or if the 5-year KFRE is greater than 5%. We investigate the impact of using the race-free eGFR equation and KFRE on CKD diagnosis in primary care and potential referrals to the renal clinic. METHOD: Primary care records for 79% of the population of Wales (UK) are held in the electronic health records repository Secure Anonymised Information Linkage Databank (SAIL). We studied serum creatinine values and urine albumin-creatinine ratios (uACRs) from 1 January 2013 to 31 December 2020. We calculated eGFR values using three equations: MDRD, CKD-EPI 2009 and (race-free) CKD-EPI 2021. Using the different equations, we compared the numbers of patients with incident eGFR <60 mL/min/1.73 m 2 and incident eGFR < 30 mL/min/1.73 m 2 (i.e. their eGFR fell from above to below these values for more than 3 months). For each year from 2013 to 2020, we identified the patients with prevalent eGFR 30–60 mL/min/1.73 m 2 those with annual uACR testing and those who met referral criteria by A) eGFR decline and B) KFRE without eGFR decline. RESULTS: There were 121 471 patients with prevalent CKD between 2013 and 2020. eGFR values were lowest using the MDRD equation (median 47.1 mL/min/1.73 m 2 IQI 39.7–51.9) and highest with the CKD-EPI 2021 equation (median 50.0 mL/min/1.73 m 2 IQI 41.6–55.3). Changing between these two equations would have led to a 17.6% reduction in incident eGFR < 60 mL/min/1.73 m 2 and a 7.5% reduction in incident eGFR < 30 between 2013 and 2020 (Figure 1 ). The rate of annual uACR testing fell from 46.3% in 2013 to 25.3% in 2019 (Figure 2 ). eGFR and uACR testing were reduced further in 2020 during the COVID-19 pandemic. Patients without diabetes and older patients were the least likely to have had uACR testing at any time: for example, amongst those aged 60–70 years, 90.0% of those with diabetes had uACR testing at any time compared to 42.7% of those without diabetes; amongst those aged over 80 years, 79.1% of those with diabetes were tested compared to 32.7% of those without diabetes. In 2019 (the last year before the COVID-19 pandemic), 787/61 721 (1.3%) patients with CKD stage 3 met referral criteria by eGFR decline and an additional 587 (1.0%) by KFRE without eGFR decline. CONCLUSION: Using the race-free eGFR equation will reduce diagnoses of incident eGFR < 30 warranting referral to specialist renal clinics. KFRE can be used to identify a significant number of patients at heightened risk of kidney failure, and these numbers may be higher if more uACR testing was performed. Annual uACR testing rates are low, especially in those without diabetes and in older adults. eGFR and uACR testing were markedly reduced during the COVID-19 pandemic in 2020 as most routine disease monitoring stopped. Expanding uACR testing in primary care (particularly in those without diabetes and in older adults) and using KFRE may improve the identification of individuals at risk of progressive kidney disease, but this is challenging during the COVID-19 pandemic.